Analisis Perbandingan Pendapatan Padi Sawah Berdasarkan Status Kepemilikan Lahan Di Desa Mogoyunggung Satu Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Sondakh, Chiko; Tangkere, Ellen Grace; Benu, Noortje Marsellanie (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the income of paddy rice farming in Mogoyunggung Satu (I) Village, Dumoga Timur District, Bolaang Mongondow Regency. The data used in this research are primary data and secondary data. Primary data obtained from direct interviews with farmers using a questionnaire. The number of samples in this study were 15 farmer respondents from a total of 198 heads of farming families, determined by purposive sampling, namely sampling on purpose or based on need. The criteria for farmers taken are representatives from each environment, namely those who are still running their farming businesses amidst the large number of farming communities who are currently turning into miners. other people's land then pays rent and 5 sharecroppers work on other people's land with a profit-sharing system. The results of research conducted in the Village of Mogoyunggung Satu (I) average revenue of Rp. 25,500,000, with an average cost of Rp. 5,708,917, the cost of renting land per hectare is IDR 2,000,000/harvest. And the profit sharing cost is 70:30 where the land owner gets 30% of the agricultural produce. Fewer expenses are from those who use family labor so that it reduces labor costs more.